Stability of neuropsychological test performance in older adults serving as normative controls for a study on postoperative cognitive dysfunction - Feinkohl, Insa; Borchers, Friedrich; Burkhardt, Sarah; Krampe, Henning; Kraft, Antje; Speidel, Saya; Kant, Ilse M. J.; van Montfort, Simone J. T.; Aarts, Ellen; Kruppa, Jochen; Slooter, Arjen; Winterer, Georg; et al. (BMC research notes, 2020)
Objective Studies of postoperative cognitive dysfunction (POCD) rely on repeat neuropsychological testing. The stability of the applied instruments, which are affected by natural variability in performance and measurement imprecision, is often unclear. We determined the stability of a neuropsychological test battery using a sample of older adults from the general population. Forty-five participants aged 65 to 89 years performed six computerized and non-computerized neuropsychological tests at baseline and again at 7 day and 3 months follow-up sessions. Mean scores on each test were compared across time points using repeated measures analyses of variance (ANOVA) with pairwise comparison. Two-way mixed effects, absolute agreement analyses of variance intra-class correlation coefficients (ICC) determined test–retest reliability. Results All tests had moderate to excellent test–retest reliability during 7-day (ICC range 0.63 to 0.94; all p < 0.01) and 3-month intervals (ICC range 0.60 to 0.92; all p < 0.01) though confidence intervals of ICC estimates were large throughout. Practice effects apparent at 7 days eased off by 3 months. No substantial differences between computerized and non-computerized tests were observed. We conclude that the present six-test neuropsychological test battery is appropriate for use in POCD research though small sample size of our study needs to be recognized as a limitation. Trial registration ClinicalTrials.gov Identifier NCT02265263 (15th October 2014)